Effect of pressure on the characteristics of Schottky barrier diodes made of overcompensated semiconductor - Vlasov, S.I.; Saparov, F.A.; Ismailov, K.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
We studied the effect of uniform compression on characteristics of Au–n-Si
Schottky barrier diodes made of overcompensated semiconductor. It is shown that
overcompensation is caused by formation of structural defects owing to thermal
treatment of the initial silicon wafers.